Lies and epiphanies composers and their inspiration from Wagner to Berg - Walton, Chris 1963- (Univ. of Rochester Press, 2014)
"Lies and Epiphanies" offers case studies of "inspiration" in five composers -- Richard Wagner, Gustav Mahler, Wilhelm Furtwängler, Richard Strauss, and Alban Berg. Their own tales of their "epiphanies" played a determining role in the reception history of their works: the finale of Mahler's Second Symphony was supposedly inspired by a "lightning bolt" of inspiration at the funeral of Hans von Bulow, while Alban Berg's Violin Concerto was purportedly his direct response to the tragic early death of Alma Mahler's daughter. Chris Walton looks behind these lightning bolts to explore instead the composers' dual roles as authors and self-commentators, laying bare the fissures and inconsistencies within their testimonies and revealing how the supposedly extrarational world of creative inspiration intersects with the highly rational world of money and politics. As Walton points out, It has often been the composer himself who was intent on imposing on his audience an interpretation of a work and its genesis that was as superficial as his score itself is not. This study seeks to answer why. Chris Walton teaches music history at the Basel University of Music in Switzerland. He is the author of "Othmar Schoeck: Life and Works" (University of Rochester Press, 2009) and "Richard Wagner's Zurich: The Muse of Place" (Camden House, 2007).
Rez.: The Wagner journal 9 (2015),1, S. 82-86 (David Matthews)
Richard Wagner's dynastic dreams -- Gustav Mahler's resurrection and the apostolic succession -- Of forked tongues and angels : Alban Berg's violin concerto -- Wilhelm Furtwängler and the return of the muse -- Here comes the sunset : the late and the last works of Richard Strauss -- Postlude : the telephone call
Keywords: Mahler, Gustav -- 1860-1911; Wagner, Richard -- 1813-1883; Furtwängler, Wilhelm -- 1886-1954; Strauss, Richard -- 1864-1949; Berg, Alban -- 1885-1935; Offenbarung; Komponist; Kreativität; Komposition -- Musik; Inspiration